Purification and characterization of H.8 antigen from group B Neisseria meningitidis. - Bhattacharjee, A K (1988)
The surface antigen (H.8) common to the pathogenic Neisseria species was purified by a simple procedure by use of high-performance liquid chromatography. The purified H.8 antigen was characterized as to its amino acid composition, susceptibilities to several proteolytic enzymes, isoelectric point, and susceptibilities to an acid and a base. The amino acid composition of purified H.8 antigen from two strains of Neisseria meningitidis group B, namely, 44/76 and 8047, were compared. It was found that glutamic acid, alanine, and proline accounted for about 80% of the total amino acids in each case. A preliminary analysis of the lipid content of this protein was made. It showed the presence of a lipid component that moves between C9 and C11 straight-chain fatty acids in the gas chromatograph. Limited amino acid sequence data were obtained by sequencing a fragment of the H.8 antigen that was isolated after partial acid hydrolysis. The H.8 antigen epitope was found to be labile to treatment with both a mild acid and a mild base.